The interplay of national distances and regional networks: Private equity investments in emerging markets - Mingo, Santiago; Morales, Francisco; Dau, Luis Alfonso (Journal of International Business Studies, 2018)
Integrating social network theory with the literature on national distance, we examine how the investment strategy followed by a private equity (PE) firm in an emerging market is affected by the interplay between two important types of national distances – institutional and geographic – and the firm’s centrality in the regional syndication network. Covering over 5,000 investment transactions, we use a dataset of more than 500 PE firms based in both developed and emerging markets targeting three emerging market regions – Latin America, Southeast Asia, and Eastern Europe – from 1996 to 2011. The results show that, depending on the level of centrality of PE firms in regional syndication networks, institutional and geographic distances can have differing effects – both in magnitude and direction – on their investment strategies in emerging markets. Moreover, these effects are contingent on whether the PE firm is from a developed market or an emerging market. We conclude that different types of national distances can operate in dissimilar ways depending on (1) firm-level factors defined at the regional level – such as centrality in the regional syndication network – and (2) the developed market or emerging market nature of the PE firm.